(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The studied problem is urgent, as one of the most common complications of upper airway resistance syndrome (UARS) is chronic insomnia. It constitutes a serious medical and social problem considering a group at risk (children and adolescents). This article is aimed at the determination of the effect produced by the distal position of the lower jaw (distocclusion) on the UARS. The leading method is processing of data obtained during cephalometric studies that enables the determination of the anteroposterior position of the lower jaw, craniocervical compensation, and diameter of the upper airways at the tongue base level. During the study it was found out that distocclusion is a direct factor that promotes UARS. This is proved by the luminal narrowing of the upper airways (8.1-9.4 mm) in these patients. The craniocervical angle was greater than 1050, indicating compensatory changes in the atlanto-occipital joint. The article can be useful for orthodontists, somnologists, ENT specialists, pediatricians, podiatrists, and osteopathologists during an examination and provision of complex aid to children and adolescents.